Skrining Fungsi Tiroid pada Pasien In Vitro Fertilization (IVF): Sebuah Pendekatan Klinis - M. Adi Firmansyah (MEDICINUS, 2025)
The success of in vitro fertilization (IVF) programs is significantly influenced by hormonal balance, in which thyroid function plays a crucial role. Thyroid disorders, both hypothyroidism and hyperthyroidism, have been shown to decrease thechances of pregnancy and increase the risk of miscarriage, making screening as an essential step before commencing an IVF cycle. The primary assessment involves measuring thyroid-stimulating hormone (TSH) levels, with an ideal targetbelow 2.5 mU/l to create an environment conducive for embryo implantation. The clinical approach depends to the TSH results and thyroid peroxidase antibodies (TPO-Ab) test. The presence of positive TPO-Ab status increases the risk of implantation failure, often necessitating low-dose levothyroxine therapy. If TSH levels are above 4.5 mU/l (hypothyroidism) or low (hyperthyroidism), the IVF cycle should be postponed until thyroid function is controlled to avoid complications. Therefore, the optimization of thyroid function through TSH screening, TPO-Ab testing, and appropriate intervention is a key pillar of IVF preparation, requiring collaboration between fertility specialists and internists or endocrinologists to maximize the chances of pregnancy.